Preparation of nitrogen-doped porous carbons for high-performance supercapacitor using biomass of waste lotus stems. Issue 13 (12th February 2018) - Yan, Song; Lin, Jingjing; Liu, Ping; Zhao, Zhicheng; Lian, Jun; Chang, Wei; Yao, Lu; Liu, Yueran; Lin, Hualin; Han, Sheng
Abstract : In this study, advanced nitrogen-doped porous carbon materials for supercapacitor was prepared using low-cost and environmentally friendly waste lotus stems (denoted as LS-NCs). Abstract : In this study, advanced nitrogen-doped porous carbon materials for supercapacitor was prepared using low-cost and environmentally friendly waste lotus stems (denoted as LS-NCs). Nitrogen in the surface functionalities of LS-NCs was investigated using X-ray photoelectron spectroscopy analysis. The sum of pyridine nitrogen (N-6) and pyrrolic/pyridinic (N-5) contents accounted for 94.7% of the total nitrogen and significantly contributed to conductivity. Pore structure and surface area of activated carbons were measured using the Brunauer–Emmett–Teller method. A maximum specific surface area of 1322 m 2 g −1 was achieved for LS-NCs. The porous carbons exhibited excellent electrochemical properties with a specific capacitance of 360.5 F g −1 at a current density of 0.5 A g −1 and excellent cycling stability (96% specific capacitance retention after 5000 cycles). The above findings indicate that taking advantage of the unique structure of abundant waste lotus stem provides a low-cost and feasible design for high-performance supercapacitors.